Politeness theory applied to the teaching of the Imperative Mood in English as a Foreign Language classes: a textbook analysis - Aldrovandi, Makeli (BELT - Brazilian English Language Teaching Journal, 2014)
This paper consists of five parts. Initially, the concept of Pragmatics is presented. Afterwards, a bibliographic review on Politeness Theory is done (Brown & Levinson, 1987). Following that, the National Curricular Parameters (PCN) are analyzed as well as what they suggest to the teaching of a foreign language in Brazilian High Schools, regarding the competences to be developed by the students on this level, as well as the inclusion of the teaching of Foreign Language in a wider area of knowledge, named Language, codes and their technologies. The criteria that the Guide of the National Textbook Program (PNLD) uses to indicate the collections that may be adopted by the public schools in the country are verified as well. Based on the PCN and the PNLD Guide, an analysis of two textbooks is carried out. These textbooks are on the list that was approved by the Ministry of Education to be distributed to the schools. The analysis aims at verifying whether there is coherence between the PCN and the textbooks. We have come to the conclusion that, even though the textbooks have a great variety of activities which comprehend the abilities of speaking, writing, listening and reading, they still treat grammar as an element apart, without contextualization nor application to real life interaction. Finally, some suggestions are made about how to include Pragmatics, specifically, Politeness Theory in foreign language classes in High School, starting from what the textbooks themselves offer the students.